A Incidence Of Neonatoric Asphicia In Pregnant Women With Severe Pre-Eclamsia Based On Age Classification - Umami, Riza (Jurusan Kebidanan Poltekkes Kemenkes Sorong, 2024)
One of the factors that causes pre-eclamsia is age < 20 and ≥ 35 years. Pre-eclampsia can result in complications in the newborn, namely asphyxia neonatorum. The aim of this study was to analyze the differences and the risk of neonatal asphyxia in PEB pregnant women by age group. This research is a comparative study with a retrospective approach. The population in this study was 134 women who gave birth with PEB, using Simple Random Sampling and obtained 100 responden. Instrument uses a checklist. Data analysis using Chi Square K Sample and Odds Ratio. The analysis of the Chi Square K test, obtained X² count=25.612 > X² table=9.4877 (α= 0.05) so it can be decided that H0 rejected, this means that there are differences in the incidence of asphyxia neonatorum in pregnant women with PEB based on age classification and the results of the Odds Ratio are 6.83. The age of the mother with PEB was more common in the RA group, but the YMA and AMA group with PEB gave birth to more asphyxia neonatorum. YMA group and AMA group have a 6.8 times higher risk of giving birth to neonates with asphyxia neonatorum compared to RA group.